2021
DOI: 10.1016/j.radcr.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Two Rare Entities in One Patient: Mucinous Tubular and Spindle Cell Carcinoma of the Kidney and Peritoneal Adenomyomas

Abstract: Mucinous tubular and spindle cell carcinoma of the kidney is a rare subtype of renal cell carcinoma, that is believed to portend a favorable prognosis. Adenomyomas are benign tumors that typically arise from the myometrium. Extrauterine adenomyomas are extremely rare, with only a few cases reported in the literature. Here, we present an unusual case of a 46-year-old woman, with an incidentally detected bulky interpolar left kidney mass measuring 12 cm and multiple lobulated coalescent per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition, the tumor is located in the renal parenchyma with expansive growth and a cystic-solid tumor is located in the renal parenchyma with expansive growth and a cystic-solid tumor with a clear boundary as determined by imaging. Plain CT scans are generally isodense or have low density [9]. Enhanced CT showed that the density of the tumor was signi cantly lower than that of the renal cortex and medulla [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor is located in the renal parenchyma with expansive growth and a cystic-solid tumor is located in the renal parenchyma with expansive growth and a cystic-solid tumor with a clear boundary as determined by imaging. Plain CT scans are generally isodense or have low density [9]. Enhanced CT showed that the density of the tumor was signi cantly lower than that of the renal cortex and medulla [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor is located in the renal parenchyma with expansive growth and a cystic-solid tumor with a clear boundary as determined by imaging. Plain CT scans are generally isodense or have low density (10). Enhanced CT showed that the density of the tumor was significantly lower than that of the renal cortex and medulla (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathophysiology underlying this association is unknown, the prevalence of concurrent EA and malignancy deserves the attention of clinicians to further investigate the patients affected by EA and vice versa. 42,51,57,63,81,82,89,90 Further studies are needed to assess the relationship between EA and malignancy.…”
Section: Study Magnetic Resonance Imaging Features Of Extrauterine Ad...mentioning
confidence: 99%
“…In contrast, the cystic spaces appeared hyperintense on both T1 and T2 images. Considered to be an endometriotic cyst Gruttadauria 2020 26 3-cm complex mass of the right ovary, 7-cm complex mass anterior to the rectum, left adnexal mass separate from the ovary Alves 2021 90 Multiple lobulated iso-to hypodense coalescent peritoneal nodules with more expression in the greater omentum that showed moderate enhancement, suggestive of peritoneal carcinomatosis…”
Section: Study Magnetic Resonance Imaging Features Of Extrauterine Ad...mentioning
confidence: 99%
See 1 more Smart Citation